American cars past to present - DeLorenzo, Matt 1953- ([Vercelli, Italy] Edizioni White Star, 2007)
Commemorating America's ongoing interest with the automobile, offers nearly four hundred photographs, showcasing cars from every era, from the Model A Ford and the Packards of the 1930s, to Mustangs and Corvettes, to the present day
Includes bibliographical references (p. 318) and index
Keywords: Automobiles -- United States -- History; Automobiles -- United States -- History